Four genes located on a SSC2 meat quality QTL region are associated with different meat quality traits in Landrace × Chinese-European crossbred population - Cepica, S; Ovilo, C; Masopust, M; Knoll, A; Fernandez, A; Lopez, A; Rohrer, G A; Nonneman, D (Animal genetics, 2012)
Several quantitative trait loci (QTL) for different meat quality traits have been localized on the q arm of porcine chromosome 2 at position 55-78 cM. Association analyses were performed in a commercial Landrace × Chinese-European (LCE) crossbred population (n = 446) slaughtered at approximately 127 kg and an average age of 198 days with records for performance (growth, fat and meat accretion) and meat quality [intramuscular fat (IMF), Minolta L*, Minolta a*, Minolta b* and pH at 45 m]. Polymorphisms within positional candidate genes cloned from homologous regions on human chromosome 19, ubiquitin-like 5 (UBL5- AM950288:g.566G>A), resistin (RETN- AM157180:g.1473A>G causing substitution p.Ala36Thr), insulin receptor (INSR- AM950289:g.589T>C) and complement factor D (adipsin) (CFD- AM950287:g. 306C>T) were located at positions 62.1, 64.0, 68.0 and 70.7 cM respectively on the current USDA USMARC map of porcine chromosome 2 and had the following allele frequencies in the LCE: UBL5 566G - 0.57; RETN 1473G - 0.84; INSR 589C - 0.70; and CFD 306C - 0.73. The effects of alleles within the candidate genes on the recorded traits were estimated using an animal model. Significant effects (P < 0.05) were found for pH(45) in m. semimembranosus (m. sm.) (UBL5), IMF (RETN) and Minolta L* (RETN, CFD). Differences between phenotypic means of homozygotes at UBL5, RETN and either RETN or CFD explained 0.34 SD for pH(45) in m. sm., 0.47 SD for IMF and 0.68 SD for Minolta L* respectively. Suggestive effects (P < 0.10) on IMF (UBL5, CFD), Minolta a* (INSR, CFD) and Minolta b* (INSR) were also observed. Our results support the localization of further QTL for meat quality traits in this region and suggest that there are several genes affecting different meat quality traits.
Keywords: Animals; Fats; Phenotype; polymerázová řetězová reakce; Polymerase Chain Reaction; mapování chromozomů; Sus scrofa; jednonukleotidový polymorfismus; Chromosome Mapping; Gene Frequency; maso; Polymorphism, Single Nucleotide; Meat; frekvence genu; genetické asociační studie; Male; Cloning, Molecular; glukosa; Glucose; tuky; klonování DNA; Quantitative Trait Loci; fenotyp; zvířata; mužské pohlaví; lokus kvantitativního znaku; Genetic Association Studies